Pacemaker longevity: understanding what drains the battery. (2nd June 2019) - Rosling, Kieran Bose; Paton, Maria F
Abstract: Pacemaker technology has improved considerably in the last 50 years. Circuitry has become more sophisticated and devices have become smaller and more efficient. However, for the last several decades, a rise in the ageing population has meant that patients are outliving their pacemakers and requiring more surgical replacement procedures. The rise in replacement procedures has resulted in a call for improved longevity of pacemakers, which may be achieved during pre-implant decisions, smart programming, and more communication between the cardiac device industry and clinicians in order to maximise pacemaker longevity and minimise the risk to patients who may have to have their pacemakers replaced. This review explores the evolution of pacemakers, the technological factors that dictate battery longevity, the demand for greater longevity and how manufacturers and clinicians may maximise the service time of pacemaker devices.